Pengaruh Senam Irama terhadap Kemampuan Motorik Anak Usia 5 Tahun - Yuliansih, Arni; , Umi Budi Rahayu, SSt. Ft. SPd. M. Kes; , Dwi Kurniawati, SST.FT, M.Kes (2015)
Motoristhemovement ofthe bodythroughthe body'slocomotor(muscular and skeletal). And themovementis thereininvolvingmotor functionsuch as the brain, nerves, andmuscles. Children whoexperience delaysin motor skillscouldbe givenstimulationone of which isrhythmic gymnastics. Rhythmic Gymnasticsis onephysicalactivitythat iseasily followed bychildren. ntherhythmic gymnasticsthere isthe music thatmakesthe childso thatthe child wouldbehappyto followmovements inrhythmic gymnastics. The purpose ofthis studyto provewhether there is influenceandthe influence ofdifferentrhythmic gymnasticson themotor skillsof children aged5years oldin kindergartenAl-Kautsarasthe treatment group. This research isquasi-experimental approachwithpretest-posttest control group design. The sample inthis studyis based onpurposivesampling(sample design under consideration). Based on the analysisof dataonmotor skillschildrenin the treatment groupusingthe Wilcoxon test, namely, gross motorp value =0.014, fine motorp value =0.046, gross motor and fine motorp value =0.025. This shows thatHaHo accepted and rejected. Whereasin the control groupthe results ofthe analysisof dataongross motor, fine motorandgross and fine motor, with p value =1.000. This shows thatHa accepted and Hois rejectedbecausethe control groupwas not givenany treatment. While the results ofdata analysisusingMann Whitney testis ongross motorp value =0.006, fine motorp value=0.025, gross and fine motorp value =0.000. This showsthat there is adifference ineffect betweenthe treatment groupandthe control group. Therefore conclusionsof this studyishave influence pre-post testthe ofrhythmic gymnastics, and has differentinfluences between the treatment groupand the control groupsignificantmotor skillsof children aged5. Keywords: Rhythmic gymnastics, Motor skill.